Modern challenges of education and psychology of personality formation - Shpak A. S., Shpak T. V., Kuznetsova V. E., Ivanova M. E., Starkova E. N., Avilova V. V., Kulikova N. V., Mikhalchenkova N. A., Pankrateva S. G., Rezak E. V., Zalunin V. I., Pantseva E. I., Kisliakova O. P., Snezhkina L. P., Khazova A. A., Sokolova G. A., Lysenko V. V., Kostenko E. G., Ambartsumian N. A., Sudakov D. V., Sudakov D. V., Sudakov O. V., Nazliev D. K., Belov E. V., Iakusheva N. V., Belov E. V., Sudakov O. V., Shevtsov A. N., Shevtsov A. N., Iordanov K. B., Markov N., Akbarova S. N., Skibo T. I., Matveichik T. V., Chernyshev V. P., Timoshkov E. V. (Modern challenges of education and psychology of personality formation, 2020)
the paper experimentally proves the effectiveness of the method of increasing dexterity in children aged 10–11 years by means of table tennis, and provides a comparative analysis. To solve the tasks set in the study, the following methods were used: analysis of scientific and methodological literature, pedagogical testing, pedagogical experiment, and mathematical-statistical processing. The results of the study allow us to improve the methodology for conducting physical education lessons and testing coordination abilities.
Keywords: тестирование; эксперимент; координационные способности; coordination abilities; experiment; testing; настольный теннис; достоверность различия; table tennis; significance of the difference